2019
DOI: 10.1007/s10654-019-00523-4
|View full text |Cite
|
Sign up to set email alerts
|

Intake of 12 food groups and disability-adjusted life years from coronary heart disease, stroke, type 2 diabetes, and colorectal cancer in 16 European countries

Abstract: Our aim was to estimate and rank 12 food groups according to disability-adjusted life years (DALYs) from coronary heart disease (CHD), stroke, type 2 diabetes (T2D), and colorectal cancer (CRC) in 16 European countries. De novo published non-linear dose-response meta-analyses of prospective studies (based on 297 primary reports), and food consumption data from the European Food Safety Authority Comprehensive European Food Consumption Database in Exposure Assessment, and DALY estimates from the Institute for He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 33 publications
(69 reference statements)
2
29
1
Order By: Relevance
“…In addition, the Nutrition and Chronic Diseases Expert Group graded the evidence for a causal association of 10 of the 14 cardiometabolic risk associations included in the analysis as probable or convincing,65 and the World Cancer Research Fund graded all five of the cancer associations as probable or convincing 73. The relative health ranking of leading risk factors found in our analysis was similar to existing rankings that relied on different relative risk variables and exposure data 174…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, the Nutrition and Chronic Diseases Expert Group graded the evidence for a causal association of 10 of the 14 cardiometabolic risk associations included in the analysis as probable or convincing,65 and the World Cancer Research Fund graded all five of the cancer associations as probable or convincing 73. The relative health ranking of leading risk factors found in our analysis was similar to existing rankings that relied on different relative risk variables and exposure data 174…”
Section: Discussionsupporting
confidence: 80%
“…73 The relative health ranking of leading risk factors found in our analysis was similar to existing rankings that relied on different relative risk variables and exposure data. 1 74 …”
Section: Discussionmentioning
confidence: 99%
“…Another six-year follow-up study found that participants with higher rates of MD adherence showed around a 50% lower risk of developing CKD [36]. Almost half of our sample did not consume any fish or legumes, which might have affected our results given that both were shown to be associated with a lower risk of CKD [37], diabetes mellitus [38][39][40], cardiovascular disease [41,42] and dyslipidaemia [37,[43][44][45]. If our sample consumed more fish and legumes, we could have detected an even stronger association between MD and these diseases.…”
Section: Discussionmentioning
confidence: 76%
“…Diet has a substantial impact on human health. Poor dietary habits are associated with obesity and a wide range of chronic diseases, including type 2 diabetes, cancer, and cardiovascular diseases [ 1 , 2 ]. Suboptimal diet is responsible for more deaths than any other risk factor globally [ 3 ].…”
Section: Introductionmentioning
confidence: 99%